CHARACTERISTICS OF EFFECTIVE TEACHERS AND EVALUATION OF TEACHER IMAGES IN PATRICIA POLACCO’S STORY BOOKS FOR YOUNG READERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
As literature has an important role in human’s life, the use of literary works in educational settings may offer great help to parents and teachers. Especially young learners discover many new concepts and values through story books. Therefore, story books which include stories related to teacher-student relationship could be quite useful to motivate young learners for academic life. This paper aims to analyze eight teacher characters in four popular story books for ages 5-8 by Patricia Polacco in the light of the studies about effective teachers. The images of teachers have been studied in close-reading as a qualitative research method. These books tell readers the experiences of a student named Trisha in her primary and high-school years. The selected books are as follows: Thank You Mr. Falker (2012), The art of Miss Chew (2012), Mr. Wayne's Masterpiece (2014), An A From Miss Keller (2015). As a result of the study, it has been concluded that six of the teachers in these books have some important qualities of effective teachers and these books might be useful tools to create positive feelings about school and teachers for young learners.